Evaluation of the intrinsic catalytic activity of nanoparticles without prior knowledge of the mass loading. (6th July 2018) - Löffler, Tobias; Wilde, Patrick; Öhl, Denis; Chen, Yen-Ting; Tschulik, Kristina; Schuhmann, Wolfgang
Abstract : We propose a method enabling the evaluation of intrinsic catalytic activity of nanoparticles based on the diffusion-limited steady-state current. Abstract : The quantitative characterisation of electrocatalytic properties of nanoparticle catalyst materials is so far only performed for layers typically comprising additionally conducting additives and binders. We propose a method enabling the evaluation of intrinsic catalytic activity of nanoparticles based on the diffusion-limited steady-state current. In a step-after-step process, the influence of coverage on kinetic and diffusion limited current is evaluated to highlight the challenges of sub-monolayer electroanalysis. Conclusions are used to point out strategies and their limitations for qualitative and quantitative comparison of intrinsic catalytic properties. Particularly, the impact of coverage, electrode geometry, altered diffusion profile for nanoparticles and the catalyst activity and selectivity are discussed. Fundamental information about electrochemical sub-monolayer nanoparticle analysis is provided.